Tax Fair Compliance: Persepsi of Tax Correction, Public Trust, and Quality of Tax Service - Kurnia; Putu Prakasa Brahmandita (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to see the effect of perceptions of tax corruption, public trust, and quality of tax services on non-employee WPOP compliance at KPP Pratama Bandung Cicadas in 2022. This study is a quantitative study using primary and secondary data. The population used in this study is non-employee WPOP at KPP Pratama Bandung Cicadas. This study used a purposive sampling. Study data will be analyzed with descriptive statistical and multiple linear regression analyses. The results of this study explain that perceptions of tax corruption, public trust, and quality of tax services simultaneously have a significant and partial positive effect on taxpayer compliance.